The Long-term Visual Outcomes of Primary Congenital Glaucoma - Esfandiari, Hamed; Prager, Alisa; Hassanpour, Kiana; P. Kurup, Sudhi; Mets-Halgrimson, Rebecca; Yoon, Hawke; Lasky Zeid, Janice; B. Mets, Marilyn; Rahmani, Bahram (Journal of ophthalmic & vision research, 2020)
Purpose: To evaluate the long-term visual outcomes of ab externo trabeculotomy for primary congenital glaucoma (PCG) at a single pediatric ophthalmology center. Methods: In this retrospective single-center case series, data from 63 eyes of 40 patients who underwent ab externo trabeculotomy between September 2006 and June 2018 were included. The data were analyzed for best corrected visual acuity (BCVA), stereopsis, and surgical success. Kaplan–Meier analysis was performed using the surgical success criteria defined as intraocular pressure (IOP) ≤ 21 mmHg and ≥ 20% below baseline without the need for additional glaucoma surgery. Results: BCVA at the time of diagnosis was 0.37 ± 0.48 logMAR, which changed to 0.51 ± 0.56 logMAR at the final follow-up (P = 0.08). Twenty-five percent of patients had BCVA equal to or better than 20/40 at the final visit. The mean refraction at baseline was –4.78 ± 5.87 diopters, which changed to less myopic refraction of –2.90 ± 3.83 diopters at the final visit. Optical correction was prescribed in 66% of eyes at the final visit. The average final stereopsis was 395.33 sec of arc. The linear regression model showed a significant association between the surgery success rate and final BCVA as well as stereoacuity (Pvalues: 0.04 and 0.03, respectively). Intraocular pressure (IOP) decreased significantly from 29.79 ± 7.67 mmHg at baseline to 16.13 ± 3.41 mmHg at the final follow-up (P = 0.001). Conclusion: Patients with PCG can achieve an acceptable visual acuity and stereoacuity, particularly in cases of timely intervention and close follow-up.